2022
DOI: 10.1097/meg.0000000000002371
|View full text |Cite
|
Sign up to set email alerts
|

BMI is important in predicting the loss of response in inflammatory bowel disease patients on tumour necrosis factor-α inhibitors

Abstract: Study designWe performed an observational retrospective cohort study in biologic-treated patients with IBD at a tertiary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Another study also reported that IBD patients with a high BMI displayed a high rate of LOR[ 118 ]. In IBD patients treated with adalimumab, SNR was increased in those with BMI ≥ 30 kg/m 2 compared with those with BMI < 30 kg/m 2 [ 119 ].…”
Section: Predictors Of Secondary Nonresponsementioning
confidence: 99%
See 1 more Smart Citation
“…Another study also reported that IBD patients with a high BMI displayed a high rate of LOR[ 118 ]. In IBD patients treated with adalimumab, SNR was increased in those with BMI ≥ 30 kg/m 2 compared with those with BMI < 30 kg/m 2 [ 119 ].…”
Section: Predictors Of Secondary Nonresponsementioning
confidence: 99%
“…Serum albumin: In CD patients treated with certolizumab, low albumin predicted SNR[ 28 ]. Higher albumin levels were associated with lower LOR in IBD patients treated with infliximab[ 119 ]. A prospective study found that IBD patients with low albumin serum concentrations at baseline had a significantly increased risk for SNR to anti-TNF and that normalization of albumin levels during treatment did not reduce this risk[ 120 ].…”
Section: Predictors Of Secondary Nonresponsementioning
confidence: 99%